O potencial formativo da cultura pop : expressões da condição humana na contemporaneidade - Dittrich, William de Souza (2022)
This piece of work is an effort of approximation of pop culture, while contemporary cultural phenomenon, with modern formative processes. Culture, being the result of the interaction between man with another and with the world around him in a determined time, therefore, in constant mutation, expresses in symbolic form human condition itself. Contemporaneity brings with it a new cultural and artistic style, that reserving due and necessary criticism, offers a series of ludic resources, through narratives, fantasy and imagination. Such resources are capable of mobilizing subjects in the teaching and learning processes. The present dissertation takes as its guiding question the speculative hypothesis of the formative potential contained within pop culture. For such, it adopts as method bibliographic research and explores, based in the psychoanalytic theory proposed by Sigmund Freud, the relation between such culture and the new ways of expressing the symbolic, as it’s reach in relation to the formative processes. In short, it’s defended that pop culture works are possible to be analyzed and interpreted, laying bare how human condition is being expressed through them and how they promote identifications, revealing the importance of comprehending the reach of these elements in different formative spaces.